First successful treatment of epidermolytic Ichthyosis with Vunakizumab: A Case Report - Cheng, Wenjie; Pan, Chaolan; Sun, Zhe; Sun, Peiyi; Li, Jiawen; Yao, Zhirong; Wang, Xiaoxiao; Zhang, Jia (Frontiers in Immunology, 2025)
Ichthyoses, a group of skin cornification disorders caused by protein and lipid abnormalities that disrupt epidermal functions, are mainly characterized by generalized scaling. This study is the first to report the use of Vunakizumab, China’s first self-developed anti-IL-17A monoclonal antibody, in treating ichthyosis. We presented a case of a 4-year-old boy with epidermolytic ichthyosis (EI) due to a KRT1 gene mutation. Since birth, he has presented with generalized erythema, desquamation, and blister formation at the extremities. Then, palmoplantar hyperkeratosis gradually emerged, accompanied by severe pruritus. After a three-month treatment with Vunakizumab, symptoms alleviated significantly and inflammatory factor levels normalized. This not only shows the great potential of Vunakizumab in treating ichthyosis but also paves the way for further research on anti-IL-17A therapies for skin cornification disorders, offering treatment options for ichthyosis patients.